Diagnostična uporabnost določanja koncentracije lipoproteina(a) in genetske variabilnosti gena LPA - Levstek, Tina (Laboratorijska medicina, 2023)
Lipoprotein(a) (Lp(a)) is an inherited and independent risk factor for cardiovascular diseases. Lp(a) is a cholesterol-rich lipoprotein synthesized in the liver. It consists of apolipoprotein B100 and apolipoprotein(a) (apo(a)) linked by a disulfide bond. Apo(a) is encoded by LPA gene, one of the most polymorphic genes in humans, as more than 40 gene variants have been discovered. Lp(a) levels are 90% genetically determined by variants in the LPA gene and are in the atherogenic range (> 300 mg/L) in 20 to 30% of the population. In the last decade, immense progress has been made in understanding the mechanisms involved in the synthesis and metabolism of Lp(a). This has also improved the understanding of the pathophysiology of Lp(a) and the factors affecting Lp(a) concentration. Although the determination of Lp(a) is not yet standardized, from a clinical point of view it allows the identification of individuals at increased risk for cardiovascular diseases. To reduce risk, promising new therapeutic options are currently being developed to directly lower Lp(a) concentrations by targeting LPA mRNA. The aim of this article is to present the latest knowledge on the structure, synthesis, metabolism, pathophysiological mechanisms, and therapeutic options for lowering Lp(a) and to address challenges in determining Lp(a) concentration in clinical laboratories.
Keywords: ateroskleroza; dislipidemija; lipoprotein(a); srčno-žilna bolezen